Transitional changes in gastrointestinal transit and rectal sensitivity from active to recovery of inflammation in a rodent model of colitis - Yan Chen (Nature Portfolio, 2021)
Abstract Patients with ulcerative colitis are typically suspected of an inflammatory flare based on suggestive symptoms of inflammation. The aim of this study was to evaluate the impact of inflammation on colonic motility and rectal sensitivity from active to recovery of inflammation. Male rats were given drinking water with 5% dextran sulfate sodium for 7 days. Inflammation, intestinal motor and sensory functions were investigated weekly for 6 weeks. (1) The disease activity index score, fecal calprotectin and tumor necrosis factor alpha were increased from Day 0 to Day 7 (active inflammation) and then decreased gradually until recovery. (2) Distal colon transit was accelerated on Day 7, and then remained unchanged. Whole gut transit was delayed on Day 7 but accelerated from Day 14 to Day 42. (3) Rectal compliance was unaffected from Day 0 to Day 7, but decreased afterwards. (4) Rectal hypersensitivity was noted on Day 7 and persistent. (5) Plasma acetylcholine was decreased on Day 7 but increased from Day 14 to Day 42. Nerve growth factor was increased from Day 7 to Day 42. DSS-induced inflammation leads to visceral hypersensitivity that is sustained until the resolution of inflammation, probably mediated by NGF. Rectal compliance is reduced one week after the DSS-induced inflammation and the reduction is sustained until the resolution of inflammation. Gastrointestinal transit is also altered during and after active colonic inflammation.